pembelajaran Development of Integrated Learning Systems through BPPT Corporate University Design approach - edy syamsuddin; Ade Rizki (The Institute of Academic Research and Publication (IARP), 2022)
The development of integrated learning is mainstreaming various integrated educational and training performance programs so that it boosts organizational performance to be part of the optimal corporate university design approach. The development of learning from education and training and the construction of functional positions of engineering and power has been carried out but the approach that refers to the strategic model of the corporate university system so that the interrelationship of all work units gets the overall corporation. Several stages of identification up to the stage of strengthening the participation of work units related to the development of institutional human resources in the unity of performance are strongly related to various inputs that support the evaluation and control system to be more concentrated and integrated to encourage organizational performance to be stronger and prosperous. Improvements in the working order and strengthening of the internal system of integrated learning implementation provide a commitment to the need for strength that can provide institutional human resource strengthening spurring the improvement of effective and efficient organizational performance towards the professionalism of the relevant institutions in it.